THE COMMON PRIESTHOOD OF WOMEN IN THE CHURCH - Mulackal, Shalini (Asian Horizons, 2015)
Historically priesthood is a creation of cult. Almost every culture developed some form of priesthood. The notion of priesthood was different in Israel since the Israelites considered themselves as a priestly people. For Christians Jesus is the only mediator between God and humans. However, Christians share in the priesthood of Christ through their baptism and confirmation. The vocation to live as a Christian is a call to live the priesthood of Jesus who offered himself as a victim for the salvation of the world. Ministerial priesthood which developed in the church is meant to help all baptized to live their priestly call to the full. Yet undue emphasis is still given to ministerial priesthood in the church even though Vatican II emphasized the vocation of all Christians to be priests. Women in the Church live their priestly vocation seriously even though they do not often talk about it or are conscious about it. Women need to appropriate to themselves their call to participate in the priesthood of Christ on account of their baptism and live that call with full awareness.